Enantioselective Synthesis of Diazobicyclic Oxadiazines via Organocatalytic [3+3]-Cycloaddition of γ-Hydroxy-α,β-Unsaturated Carbonyls with N,N′-Cyclic Azomethine Imines - Kang, Sung Hyun; Park, Byung Jun; Kim, Sung-Gon (Synthesis, 2023)
A diastereo- and enantioselective synthesis of diazobicyclic oxadiazines was developed through an organocatalytic cycloaddition reaction. Asymmetric catalytic [3+3]-cycloaddition of γ-hydroxy-α,β-unsaturated carbonyls with N,N′-cyclic azomethine imines, using a squaramide-based catalyst, provided biologically important enantioenriched diazobicyclic oxadiazines in good yields with moderate to high diastereo- and enantioselectivities (up to 10:1 dr and 79:21 er).
Keywords: asymmetric catalysis; [3+3]-cycloaddition; N,N′-cyclic azomethine; diazobicycle; oxadiazine